Biochar application ameliorated the nutrient content and fungal community structure in different yellow soil depths in the karst area of Southwest China - Zhang, Meng; Liu, Yanling; Wei, Quanquan; Gu, Xiaofeng; Liu, Lingling; Gou, Jiulan (Frontiers in Plant Science, 2022)
Biochar is more and more produced and applied in soil, in order to satisfy the need for agricultural production and soil improvement. However, the influence of biochar on the change of nutrient content and fungal community structure in different yellow soil depths of karst area is still not clear. In this paper, soil column leaching simulation test is used to evaluate the influence of distiller's grains biochar on the soil content, enzymatic activity, fungal community diversity and structural composition. Three biochar amounts are arranged in the test, including 0% (NB), 1.0% (LB), and 4.0% (HB). Results showed that the application of biochar significantly improved the content of soil organic matter (SOM), total nitrogen (TN), available phosphorus (AP) and available potassium (AK), but reduced the content of microbial biomass carbon (MBC) and microbial biomass nitrogen (MBN), and this effect enhanced with the increasing biochar amount and soil depth. Besides, the applied biochar affected the enzymatic activity, especially the sucrase activity. Compared with the NB treatment, the application of biochar significantly affected the diversity of fungal community structure in yellow soil, and the degree of influence increased with the increase of biochar application amount. In addition, biochar changed the fungal community structure, particularly the effective inhibition on the growth and reproduction of the harmful pathogen, which increased the relative abundance of part beneficial fungi. Redundancy analysis (RDA) showed that there was a difference on the main environmental factors affecting the fungal community structure, but AK was an influence factor for all soil depths. Overall, biochar has a positive effect on improvement of the land productivity and of micro ecological environment of yellow soil, which can provide an effective management strategy for agricultural production in karst mountain area.